An Investigation of Water Diffusivity Changes along the Perivascular Space in Elderly Subjects with Hypertension - Kikuta, J; Kamagata, K; Takabayashi, K; Taoka, T; Yokota, H; Andica, C; Wada, A; Someya, Y; Tamura, Y; Kawamori, R; Watada, H; Naganawa, S; et al. (American journal of neuroradiology : AJNR, 2022)
Hypertension may be related to alterations of the glymphatic system, a waste metabolite drainage system in the brain. We aimed to investigate analysis along the perivascular space index changes in elderly subjects with hypertension. Diffusion-weighted images were acquired from 126 subjects, including 63 subjects with hypertension (25 men and 38 women; mean age, 72.45 years) and 63 age- and sex-matched controls (25 men and 38 women; mean age, 72.16 years). We calculated the analysis along the perivascular space index as a ratio of the mean of x-axis diffusivities in the projection and association areas to the mean of y-axis diffusivity in the projection area and z-axis diffusivity in the association area. The left, right, and mean analysis along the perivascular space indices of both hemispheres were compared between the hypertension and control groups using a Mann-Whitney test. The Spearman correlation coefficient was used to assess the correlation between the left, right, and mean ALPS indices and blood pressure and pulse pressure. The left ( = .011) and mean ( = .024) analysis along the perivascular space indices of the hypertension group were significantly lower than that of the control group. The left, right, and mean analysis along the perivascular space indices of all subjects were significantly negatively correlated with blood pressure values ( = -0.200 to -0.278, = .002-0.046) and pulse pressure values ( = -0.221 to -0.245, = .006-0.013). Our results are consistent with a model in which hypertension causes glymphatic dysfunction.